The Christmas toy factory - Stilton, Geronimo (New York : Scholastic, 2006)
Geronimo Stilton regrets that he is too busy to celebrate Christmas in New Mouse City and wishes he could fly to Santa's toy factory.
"English translation...by Edizioni Piemme S.p.A."--T.p. verso.
G3
Keywords: Stilton, Geronimo (Fictitious character) -- Juvenile fiction; Christmas stories; Factories -- Juvenile fiction; Mice -- Juvenile fiction; Mice -- Fiction; Christmas -- Fiction; Factories -- Fiction; Journalists -- Fiction; Adventure and adventurers -- Fiction; Humorous stories; Christmas stories